Properties of Palm Oil Fuel Ash Cement Based Aerated Concrete Panel Subjected To Different Curing Regimes - Mohd Warid, Hussin; Khairunisa, Muthusamy (Universiti Teknologi Malaysia, 2009)
Palm oil fuel ash (POFA) being disposed as profitless waste by palm oil mills throughout Malaysia has inspired researchers from Universiti Teknologi Malaysia to integrate this material in lightweight concrete production. This paper presents results on strength of aerated concrete containing POFA at various replacement levels and its application as non-load bearing wall after subjected to different curing regimes. Cubes of (70.6x70.6x70.6mm) containing 10, 20, 30, 40 and 50 percent ash replacement levels were cast and tested for compression following the procedures in BS 1881 : Part 116. Mix with 20% POFA which exhibit superior strength than any other replacement level was used to prepare panel of 540x250x25mm. The specimens were subjected to curing regimes namely; water, air, natural weather and wet dry cycle curing before the 28 days compressive strength of panels was evaluated in accordance to ASTM E72-05. This study proved that air cured panel performs better than panel subjected to other types of curing.